Transforming Classicism into Romanticism and Beyond in Goethe’s “The Roman Carnival”. - Broszeit-Rieger, Ingrid (Neophilologus, 2010)
This essay situates “The Roman Carnival,” a short narrative in Goethe’s fictional travelogue, Italian Journey, within the debate about Goethe’s relationship to classicism. I argue that this narrative evokes the structure of a Greek tragedy, but reverses retardation and catastrophe, thus creating an anti-climactic effect at the end. Therefore, this text simultaneously affirms as well as undermines its classical model. Introducing an elusive narrator, stock characters and scenes from the commedia dell’arte, Goethe continues to break classical rules and adds an undercurrent of Romantic irony to the process of signification. This unconventional textual weave of discursively juxtaposed traditions, namely narrative with drama, classical tragedy with popular comedy, and classical with Romantic elements, transforms set categories into a progressive meta-text. This meta-text transcends established formal and philosophical/theoretical paradigms by eliminating their hierarchical and historical order within the new open and multi-directional organization of the narrative.